Optimasi Iklan Perempuan Maju Digital pada Facebook Ads Manager - Laily Kurniawati; Maman Suherman (UNISBA Press, 2022)
Abstract. Women Maju Digital (PMD) is a program created by Thinkweb, as a social impact agency that has a vision and mission in the field of education and gender equality. The Digital Advancement Women Program is a special program for women who want to develop their business and learn about business in the digital era, from idea generation to branding and marketing. To promote the class so that it reaches the target market, promotional activities are needed through the advertising of Facebook Manager. As an advertiser, the skills needed to optimize ads through the Facebook Ads Manager are so that Key Performance Indicators (KPIs) can be achieved. Based on this phenomenon. So the problems in this research are formulated as follows: (1) How is the advertising planning process through the Facebook Ads Manager? (2) How is the implementation of advertising through facebook ads manager? (3) How are the results obtained from advertising through the facebook ads manager?. The author participated in the Independent Campus Internship program on Thinkweb for five months, and directly participated in optimizing the Women Maju Digital advertisements through the facebook ads manager. As for the results of the formulation of the problem that has been made, namely in advertising planning, a media planner is needed which includes all future advertising plans, and as a reference for advertisers in advertising installation and optimization. Then in the ad implementation process, advertising is done through the Facebook ads manager tool and monitored every day through daily checks, if it is felt that the ad performance is not good then an optimization process is needed. Furthermore, all advertisements that have finished their broadcast period will be made monthly reports and analyzed so that learning or learning is obtained to start in the future. Abstrak. Perempuan Maju Digital (PMD) merupakan sebuah program yang dibuat oleh Think web, sebagai agency social impact yang memiliki visi misi dibidang Pendidikan dan kesetaran gender. Program Perempuan Maju Digital adalah program khusus bagi para Perempuan yang ingin mengembangkan bisnis dan mempelajari bisnis di era digital, mulai dari pembuatan ide hingga branding dan pemasaran. Untuk mempromosikan kelas agar sampai ke target pasar yang dibutuhkan kegiatan promosi melalui pemasangan iklan facebook manager. Sebagai seorang pengiklan kemampuan yang dibutuhkan untuk mengoptimasi iklan melalui facebook ads manager agar Key Performance Indicator (KPI) dapat tercapai. Berdasarkan fenomena tersebut. Maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Bagaimana proses perencanaan iklan melalui facebook ads manager? (2) Bagaimana pelaksanaan pemasangan iklan melalui facebook ads manager? (3) Bagaimana hasil yang didapat dari pemasangan iklan melalui facebook ads manager?. Penulis mengikuti program Magang Kampus Merdeka di Think web selama lima bulan, dan secara langsung turut serta melakukan optimasi iklan Perempuan Maju Digital melalui facebook ads manager. Adapun hasil dari rumusan masalah yang telah dibuat yakni pada perencanaan iklan diperlukan media planner yang memuat semua perencanaan iklan kedepannya, dan sebagai acuan advertiser dalam pemasangan dan optimasi iklan. Kemudian pada proses pelaksanaan iklan, pemasangan iklan dilakukan melalui alat facebook ads manager dan dipantau setiap hari melalui pemeriksaan harian, jika dirasa kinerja iklan kurang baik maka diperlukan proses optimasi. Selanjutnya, semua iklan yang sudah selesai masa tayangnya akan dibuat laporan bulanan dan dianalisis sehingga didapat pembelajaran atau pembelajaran untuk memulai kedepannya.